An update on the use of immunoglobulin for the treatment of immunodeficiency disorders. (October 2014) - Albin, Stephanie; Cunningham-Rundles, Charlotte
For patients with significant antibody deficiencies, immunoglobulin therapy is the mainstay of treatment as it significantly reduces both the frequency and severity of infections. The formulations and delivery methods of immunoglobulin have evolved over time, and continued improvements have allowed for increased access to this effective medication. This review is an update on the current status of immunoglobulin therapy in immunodeficiency disorders, and discusses the mechanisms, forms and dosing, and indications for immunoglobulin replacement.